Electrical properties and subband occupancy at the (La, Sr)(Al, Ta)O3/SrTiO3 interface - Han, K. (2019)
The quasi-two-dimensional electron gas at oxide interfaces provides a platform for investigating quantum phenomena in strongly correlated electronic systems. Here, we study the transport properties at the high-mobility (La0.3Sr0.7) (Al0.65Ta0.35) O3/SrTiO3 interface. Before oxygen annealing, the as-grown interface exhibits a high electron density and electron occupancy of two subbands: higher-mobility electrons (μ1≈10^4 cm2 V−1s−1 at 2 K) occupy the lower-energy 3dxy subband, while lower-mobility electrons (μ1≈103cm2V−1s−1 at 2 K) propagate in the higher-energy 3dxz/yz-dominated subband. After removing oxygen vacancies by annealing in oxygen, only a single type of 3dxy electrons remain at the annealed interface, showing tunable Shubnikov–de Haas oscillations below 9 T at 2 K and an effective mass of 0.7me. By contrast, no oscillation is observed at the as-grown interface even when electron mobility is increased to 50 000 cm2V−1s−1 by gating voltage. Our results reveal the important roles of both carrier mobility and subband occupancy in tuning the quantum transport at oxide interfaces.